Pleural Effusion or Main Left Bronchus Mucus Obstruction: To Drain or Not to Drain? Decision-Making for Young Surgeon on Call - Danilo Coco; Silvana Leanza (Case Reports in Radiology)
Mucous plugs occur in a number of pulmonary conditions. Central right or left bronchus mucus plug causes complete pulmonary collapse making it an emergency life-threatening case. We describe the case of an 80-year-old man that, in postoperative period after a urological intervention, has had a progressive tachypnea and dyspnea during hospitalization for urological problems. Young surgeon on call was called.